124k views
0 votes
Solve the following equation for x. Show each step.
5x + 2 = 3x + 4(2x - 1)

User Millebii
by
5.2k points

2 Answers

5 votes
ANSWER: x = 1

1. Distribute the 4 into (2x-1). 5x + 2 = 3x + 8x - 4.
2. Add the like terms. 5x + 2 = 11x - 4.
3. Subtract 5x on both sides. 2 = 6x - 4.
4. Add 4 on both sides. 6 = 6x
5. Divide 6 on both sides. x = 1
User Phius
by
5.6k points
2 votes

Answer:


x=1

Explanation:

Start with:


5x+2=3x+4(2x-1)

Distribute the
4 into
(2x-1):


5x+2=3x+8x-4

Combine like terms:


5x+2=11x-4

Add
4 to both sides of the equation:


5x+6=11x

Subtract
5x from both sides of the equation:


6=6x

Divide both sides of the equation by the coefficient of
x, which is
6:


1=x

or


x=1

User Rjz
by
5.8k points